The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1126/scitranslmed.abf5264
|View full text |Cite
|
Sign up to set email alerts
|

Alloantigen-specific type 1 regulatory T cells suppress through CTLA-4 and PD-1 pathways and persist long-term in patients

Abstract: Type 1 regulatory T cells suppress alloreactive immune cells after adoptive transfer in a CTLA-4 and PD-1–mediated manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 78 publications
(144 reference statements)
7
69
2
Order By: Relevance
“…Ovalbumin-specific Tr1 cell clones were administrated to Chron's disease patients with no side effects, but limited clinical efficacy [84]. Our group developed a DC-10-based protocol to generate in vitro Ag-specific Tr1 cells [28] that have been used to prevent graftversus host disease after bone marrow transplantation [85]. Thus far, DC-10 pulsed with Ags have been used to differentiate allergen-specific Tr1 cells form allergic patients [86].…”
Section: Discussionmentioning
confidence: 99%
“…Ovalbumin-specific Tr1 cell clones were administrated to Chron's disease patients with no side effects, but limited clinical efficacy [84]. Our group developed a DC-10-based protocol to generate in vitro Ag-specific Tr1 cells [28] that have been used to prevent graftversus host disease after bone marrow transplantation [85]. Thus far, DC-10 pulsed with Ags have been used to differentiate allergen-specific Tr1 cells form allergic patients [86].…”
Section: Discussionmentioning
confidence: 99%
“…This was also accompanied by a decreased frequency of PbTII ΔSting cells producing granzyme (Gzm) B and perforin, relative to PbTII WT cells (Figure S6A-C). The expression of these cytotoxic molecules has previously been associated with both mouse and human Tr1 cells (Chen et al, 2021; Hidalgo et al, 2008). However, differences in Tr1 cells defined by LAG3 and CD49b expression were less consistent between PbTII ΔSting and PbTII WT cells (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Tr1 cells can also inhibit the activation of effector cells via binding immune checkpoint molecules such as PD-1 and CTLA-4. Chen et al ( 154 ) demonstrated that blocking CTLA-4 or PD-1/ programmed cell death ligand 1 almost completely abolished human Tr1 cell-mediated inhibition of effector T cell proliferation. Akdis et al ( 74 ) also reported that human Tr1 cells suppressed the production of IL-13 from Der p 1 or Bet v 1-specific Th2 by down-modulation of antigen-presenting cells through expressions of CTLA-4 and PD-1 on Tr1 cells.…”
Section: Immunosuppressive Roles Of Tr1 Cellsmentioning
confidence: 96%